Kalamata's kitchen : taste buds in harmony - Thomas, Sarah; Wallace, Derek; Edwards, Jo Kosmides (New York : Random House, 2022)
"Kalamata and her friends Al Dente, Kyo, Dovie, and Knox are practicing their dance routine for the upcoming talent show. But none of them agree on what the routine is missing--Dovie thinks it needs more twirls, Knox wants more break-dancing, and everyone is getting frustrated! Luckily for the Electric (Fried Chicken) Sliders (as their group is called), all the magic they need to create a great dance routine is within reach! As Kalamata, Kyo, and Al Dente transport themselves to Kyo's family's kopitiam (Malaysian coffee shop), they discover how different ingredients are made better when combined with others. When they return, the team works together to incorporate each of their ideas and moves into a routine that steals the show!"--Provided by publisher
Keywords: Talent shows -- Juvenile fiction